Contact Allergy to Hair Dyes - Uter, Wolfgang; Lepoittevin, Jean Pierre; Lidén, Carola (Springer International Publishing, 2020)
The desire to change the color of one’s own hair is probably about as old as mankind. Techniques used nowadays involve chemically active substances, mostly in terms of components of so-called oxidative or permanent hair dye cosmetic products. The reaction chemistry is briefly reviewed. Contact allergy to many of these compounds is well demonstrated experimentally and also common according to available clinical data. On a population level, contact allergy to p-phenylenediamine (PPD) affects around 1%, while with morbidity-driven selection, the prevalence of PPD contact allergy in consecutively patch-tested patients is around 4-6%. However, surveys of labelled ingredients indicate that in some European countries (in contrast to, e.g., the USA), PPD has largely been replaced by toluene-2, 5- diamine (PTD), which only partially crossreacts to PPD, and other derivatives. Evidence on the frequency of positive reactions to substances beyond PPD is available from several clinical studies which are presented here. In conclusion, patch test diagnosis has to rely on an adequate hair dye/hair cosmetics series, such as the one suggested recently and presented here. The components of non-oxidative hair dye products need further investigation.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Contact dermatitis; Hair dye; Patch testing